2022
DOI: 10.2147/jir.s389017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Telmisartan and Quercetin in 5 Fluorouracil-Induced Renal Toxicity in Rats

Abstract: The present study was designed to evaluate the possible synergistic effects of telmisartan and quercetin in 5 fluorouracil (5-FU) induced nephrotoxicity in rats. Methodology: Forty male rats were randomly divided into five groups: The negative control group, the positive control group that received 5-FU, the telmisartan group, receiving 10 mg/kg, the quercetin group, receiving 80 mg/kg, and the combination of telmisartan and quercetin group. All the treatments were given orally for 14 days. A single intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Conversely, the DMH/KMP group exhibited increased infiltration of inflammatory cells, hinting at the protective role of KMP in kidney health. The DMH/5-FU(HD)/KMP group demonstrated mild glomerular degeneration, congestion, and tubular degeneration, implicating high-dose 5-FU treatment in renal damage 43 . Most intriguingly, the DMH/5-FU(LD)/KMP group showcased a normal renal morphology with no evidence of inflammation or necrosis, thereby highlighting a potentially less damaging response compared to the high-dose regimen.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the DMH/KMP group exhibited increased infiltration of inflammatory cells, hinting at the protective role of KMP in kidney health. The DMH/5-FU(HD)/KMP group demonstrated mild glomerular degeneration, congestion, and tubular degeneration, implicating high-dose 5-FU treatment in renal damage 43 . Most intriguingly, the DMH/5-FU(LD)/KMP group showcased a normal renal morphology with no evidence of inflammation or necrosis, thereby highlighting a potentially less damaging response compared to the high-dose regimen.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3A, quercetin pre-treatment significantly decreased the sCr in AKI (SMD: 2.73, 95% CI: 3.66, −1.80; p < 0.01; I 2 = 80%) (Chander et al, 2005;Kusumoto et al, 2011;Sanchez-Gonzalez et al, 2011;Nabavi et al, 2012;Chen et al, 2014;Saito et al, 2014;Li et al, 2016;Gholampour and Sadidi, 2018;Lucida et al, 2019;Tan et al, 2019;Tan et al, 2020;El-Sayed et al, 2021;Goncalves et al, 2021;Rahdar et al, 2021;Wang et al, 2020;Ali et al, 2022;Vazquez-Atanacio et al, 2022;Yilmaz et al, 2022). Furthermore, sensitivity analysis results showed no variation in the pooled estimate of sCr, suggesting that quercetin has a robust effect in reducing sCr in AKI animals (Figure 3B).…”
Section: Serum Creatininementioning
confidence: 88%
“…This meta-analysis included 18 research with 278 animals (Chander et al, 2005;Kusumoto et al, 2011;Sanchez-Gonzalez et al, 2011;Nabavi et al, 2012;Saito et al, 2014;Li et al, 2016;Gholampour and Sadidi, 2018;Shu et al, 2018;Tan et al, 2019;Tan et al, 2020;El-Sayed et al, 2021;Goncalves et al, 2021;Rahdar et al, 2021;Wang et al, 2020;Ali et al, 2022;Vazquez-Atanacio et al, 2022;Yilmaz et al, 2022). The result showed that quercetin administration obviously decreased BUN (SMD = −4.78; 95% CI: 6.45, −3.12; p < 0.01; I 2 = 84%) in AKI animals (Figure 2A).…”
Section: Blood Urea Nitrogenmentioning
confidence: 98%
See 1 more Smart Citation
“…After 14 days of acclimatization, the animals were divided into nine groups (Gp) with six rats each as follows: Gp I (VC): intragastric administration of saline for 21 days; Gp II (PC): intragastric administration of chitosan polymer for 21 days; Gp III (TEL): intragastric administration of 10 mg/kg of telmisartan (TEL) for 21 days ( Ali et al, 2022 ); Gp IV (free Sp): intragastric administration of 300 mg/kg of free Sp extract for 21 days ( Khalil et al, 2020 ); Gp V (nano Sp): intragastric administration of 100 mg/kg of nano Sp extract for 21 days ( Hardiningtyas et al, 2022 ); Gp VI (Cyclo): one intraperitoneal injection of 200 mg/kg Cyclo on day 18 of the experiment ( Bhatt et al, 2017 ); Gp VII (TEL + Cyclo): intragastric administration of 10 mg/kg of TEL for 21 days plus one intraperitoneal injection of Cyclo (200 mg/kg) on day 18; Gp VIII (free Sp + Cyclo): intragastric administration of 300 mg/kg of free Sp extract for 21 days plus one intraperitoneal injection of Cyclo (200 mg/kg) on day 18; Gp IX (nano Sp + Cyclo): intragastric administration of 100 mg/kg of nano Sp extract for 21 days plus one intraperitoneal injection of Cyclo (200 mg/kg) on day 18.…”
Section: Methodsmentioning
confidence: 99%